Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Kain Tenun di Dusun Sade Lombok - Wardani , Linda; Putra, Komang Endrawan Sumadi (Jurnal Manajemen Perhotelan dan Pariwisata, 2023)
This study aims to examine the effect of product quality and price on purchasing decisions, either simultaneously or partially. The research design used in this study is causal quantitative. The subjects in this study were consumers who had bought woven fabrics in Sade Lombok, aged 20-50 years. The object of this research is Product Quality, Price and Purchase Decision. Determination of the sample in this study using a purposive sampling technique. The number of samples used was 90 respondents. The instrument used in data collection was a questionnaire and the data analysis technique used was multiple linear regression analysis. The results of this study are (1) product quality and price have a significant effect on purchasing decisions, (2) product quality has a positive and significant effect on purchasing decisions, (3) price has a positive and significant effect on purchasing decisions